Initial Offer Precision and M&A Outcomes - Petri Hukkanen; Matti Keloharju (Research Institute of Industrial Economics (IFN), 2014)
Building on recent research in social psychology, this paper analyzes the link between the precision of initial cash offers and M&A outcomes. About one-half of the offers are made at the precision of one or five dollars per share, and an additional one-third at the precision of half dollar or one quarter. The practice of making offers at granular price per share levels is associated with the following unfavorable outcomes for the bidder: (1) higher purchase price for target shares, (2) lower probability to complete the deal, and (3) lower announcement return. A median-sized offer made at the precision of one or five dollars per share is associated with a 45 million dollars higher expected transaction price than one made at a precision greater than one quarter. Our results are consistent with the idea that bidders have learned to avoid making offers at the most granular level.
Keywords: G00; G02; G34; 330; Initial Offer Precision; Mergers and Acquisitions